Sensing the Local Magnetic Environment through Optically Active Defects in a Layered Magnetic Semiconductor - Klein, Julian; Song, Zhigang; Pingault, Benjamin; Dirnberger, Florian; Chi, Hang; Curtis, Jonathan B; Dana, Rami; Bushati, Rezlind; Quan, Jiamin; Dekanovsky, Lukas; Sofer, Zdenek; Alù, Andrea; et al. (ACS nano, 2023)
Atomic-level defects in van der Waals (vdW) materials are essential building blocks for quantum technologies and quantum sensing applications. The layered magnetic semiconductor CrSBr is an outstanding candidate for exploring optically active defects because of a direct gap, in addition to a rich magnetic phase diagram, including a recently hypothesized defect-induced magnetic order at low temperature. Here, we show optically active defects in CrSBr that are probes of the local magnetic environment. We observe a spectrally narrow (1 meV) defect emission in CrSBr that is correlated with both the bulk magnetic order and an additional low-temperature, defect-induced magnetic order. We elucidate the origin of this magnetic order in the context of local and nonlocal exchange coupling effects. Our work establishes vdW magnets like CrSBr as an exceptional platform to optically study defects that are correlated with the magnetic lattice. We anticipate that controlled defect creation allows for tailor-made complex magnetic textures and phases with direct optical access.
Keywords: sensing; defect emission; magnetic semiconductor; defect magnetic order; CrSBr; van der Waals magnet; magnetic correlation